PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIFTIPE STUDENT TEAMS ACHIEVEMENT DIVISIONSISWA KELAS VI DI SDN 169/II LUBUK TELAU - Suci amilia; Nurlev avana; Subhanadri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by the low learning process and outcomes of Mathematics in grade VI at SDN 169/II Lubuk Telau, this is evidenced by the results of initial observations conducted by researchers from 10 students only 40.00% obtained scores in the achievement criteria. The cause is the learning process is still centered on the teacher and the learning model used by the teacher is not varied. The purpose of the research is to improve the learning process and outcomes of Mathematics using the Student Teams Achievement Division model.The research method used in this study is classroom action research, the subjects of this study were 10 sixth grade students of SDN 169/II Lubuk Telau. In the implementation of the research conducted by the researcher consisted of 2 cycles. Each cycle consisted of 2 meetings, each meeting consisting of 4 stages, namely planning, implementation/action, observation/observation, and reflection. This research was conducted in the first semester of the 2025 academic year at SDN 169/II Lubuk Telau. The research data were collected through observation, tests, and documentation. The results of the study indicate that the use of the Student Teams Achievement Division model can improve the process and results of Mathematics learning in class VI of SDN 169/II Lubuk Telau. This can be seen from the increase in educator observations in cycle I with an average percentage of 83.25% and in cycle II with an average percentage of 94.4% with the Very Good category. The increase in the student learning process, in cycle I reached 62.5% categorized as Fairly Good and in cycle II increased to 82.5% with the Good category. The increase in student learning outcomes in cycle I reached 40% categorized as Very Poor and cycle II reached 80% with the Good category.